Category Shift in the Translation of Hemingway’s The Old Man and the Sea into Indonesian by English Literature Students - Johannes Joseph (JET (Journal of English Teaching), 2025)
This study aims at analyzing the types of category shift in the translation of Hemingway’s The Old Man and the Sea by English Literature Students. The method employed is descriptive qualitative. The data are analyzed by using Catford’s category shift which consists of class, unit, intra-system and structure shifts. This research shows that structure shift is applied more often in the translation with 56 data (51%), followed by intra-system shift with 24 data (23%), unit shift with 23 data (22%), and class shift with 5 data (4%). The higher frequency of structure shifts in translation is often due to significant linguistic differences between the source and target languages, requiring adjustments for accurate meaning and natural flow. Additionally, these shifts enhance clarity and readability, making the text more comprehensible for the target audience. Cultural and contextual adaptations also play a role, ensuring the translation aligns with the norms and expectations of the target language's audience.